2014
DOI: 10.1080/02640414.2013.855803
|View full text |Cite
|
Sign up to set email alerts
|

Changes in transverse relaxation time of quadriceps femoris muscles after active recovery exercises with different intensities

Abstract: The purpose of this study was to examine the changes in the metabolic state of quadriceps femoris muscles using transverse relaxation time (T2), measured by muscle functional magnetic resonance (MR) imaging, after inactive or active recovery exercises with different intensities following high-intensity knee-extension exercise. Eight healthy men performed recovery sessions with four different conditions for 20 min after high-intensity knee-extension exercise on separate days. During the recovery session, the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
(80 reference statements)
1
12
0
Order By: Relevance
“…More specifically, transverse relaxation time (T 2 )-weighted MRI can provide information on water content of muscle tissue given as a T 2 value, which can be then used as an index of the inflammatory edema induced by eccentric exercise 30, 31 . It has been reported that T 2 increases immediately post-exercise regardless of muscle damage 3135 and subsides within as early as few minutes 36, 37 , and it increases again ≥~12 h post-exercise if muscle is damaged 36, 37 . For example, Ochi et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, transverse relaxation time (T 2 )-weighted MRI can provide information on water content of muscle tissue given as a T 2 value, which can be then used as an index of the inflammatory edema induced by eccentric exercise 30, 31 . It has been reported that T 2 increases immediately post-exercise regardless of muscle damage 3135 and subsides within as early as few minutes 36, 37 , and it increases again ≥~12 h post-exercise if muscle is damaged 36, 37 . For example, Ochi et al .…”
Section: Introductionmentioning
confidence: 99%
“…36 reported that T 2 significantly increased immediately post-exercise in the elbow flexors of both arms that performed either maximal concentric or eccentric contractions (5 sets × 6 reps), but T 2 returned to baseline at 1 day post-exercise in the concentrically exercised arm (without DOMS) while it remained elevated at 1, 3, and 5 days post-exercise in the eccentrically exercised arm (with DOMS). Thus, it is considered that the acute T 2 increase is associated with muscle activation during exercise 3135 , and the delayed T 2 increase is a consequence of muscle damage (inflammatory edema), the degree of which is often greater than the acute one 31, 32, 37 . To support the usefulness of T 2 as an index of muscle damage, high correlation ( r  > 0.9) has been reported between changes in T 2 and plasma CK activity measured within several days after eccentric exercises 30, 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the results could be applicable to the individuals who are diverse inˆber types, and would suggest that the higher e‹ciency at the higher work rate is derived with the magnitude of rate coding in Type Iˆbers. The eŠect of active recovery has been evaluated with light to moderate exercise intensity standardized by VT (Koizumi, K., et al (2011)) or LT (Mukaimoto, T., et al (2014)), and showed lower blood lactate concentration with the active condition. Mukaimoto, T., et al (2014) also compared 50z, 70z and 100zLT and showed the lower the intensity, the lower the lactate concentration.…”
Section: The E‹ciencies At Dišerent Work Rates Below Vtmentioning
confidence: 99%
“…The eŠect of active recovery has been evaluated with light to moderate exercise intensity standardized by VT (Koizumi, K., et al (2011)) or LT (Mukaimoto, T., et al (2014)), and showed lower blood lactate concentration with the active condition. Mukaimoto, T., et al (2014) also compared 50z, 70z and 100zLT and showed the lower the intensity, the lower the lactate concentration. In the present study, WE showed sig-niˆcantly lower value in 50zVT compared to the higher intensities of 75z and 100zVT.…”
Section: The E‹ciencies At Dišerent Work Rates Below Vtmentioning
confidence: 99%
See 1 more Smart Citation